1980
DOI: 10.1111/j.1399-3054.1980.tb03213.x
|View full text |Cite
|
Sign up to set email alerts
|

Redistribution of potassium, boron, iron, magnesium and calcium in apple trees determined by an indirect method

Abstract: The intensity of the process of redistribution of the elements potassium, boron, iron, magnesium and calcium was determined by following the rate of accumulation of these elements into the fruits of apple (Malus domestica Borkh.) trees. The determination is based on the assumption that the process of primary distribution via the xylem becomes relatively unimportant with respect to supply along the phloem during the period of fruit growth. Thus a decreasing rate of accumulation for a phloem‐immobile and xylem‐m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

1984
1984
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(3 citation statements)
references
References 7 publications
0
2
0
1
Order By: Relevance
“…Thus, the B absorption, via leaf application, can be influenced by different factors: species (Goor & Lune 1980), concentration of the application solution, leaf cuticle permeability, relative air humidity, leaf age (Shu et al 1994), and also amount of applications. Basso & Suzuki (2001) reported that there are usually no problems of B deficiency in soils well provided with organic matter and pH less than 7, differing from the results observed in the present study.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the B absorption, via leaf application, can be influenced by different factors: species (Goor & Lune 1980), concentration of the application solution, leaf cuticle permeability, relative air humidity, leaf age (Shu et al 1994), and also amount of applications. Basso & Suzuki (2001) reported that there are usually no problems of B deficiency in soils well provided with organic matter and pH less than 7, differing from the results observed in the present study.…”
Section: Resultsmentioning
confidence: 99%
“…In this context, the translocation of this element may confer better tolerance to deficiency or toxicity (BROWN;SHELP, 1997). However, depending on the species, it is considered a low mobile or immobile element in phloem (VAN GOOR;LUNE, 1980;BROWN;SHELP, 1997). In summary, B translocation involves active efflux channels and pumps with specific expression patterns depending on internal and external factors (LEAUNGTHITIKANCHANA et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Estes compostos são itóis (álcoois de açúcar) como: sorbitol (macieira), manitol (brócolis) e dulcitol (Dordas et al, 2001). Os itóis são considerados compostos de estoque formados durante o processo fotossintético e transportados pelo floema em plantas superiores, sendo utilizados na nutrição heterotrófica e na osmorregulação (Loescher et al, 1995). O B se moveria, portanto, ligado a esses itóis.…”
Section: Introductionunclassified